Las relaciones interpersonales en el proceso de enseñanza aprendizaje en estudiantes del sexto grado de la escuela Dr. Ángel Felicísimo Rojas. - Gonzaga Abad, Jessica Isabel (2022)
The research work entitled: Interpersonal relationships in the teaching-learning process in sixth grade students of the Dr. Ángel Felicísimo Rojas school, had as general objective, to analyze the incidence of interpersonal relationships in the teaching-learning process for a harmonious coexistence. In order to carry out the research, the pre-experimental methodology was applied, due to the fact that the study of the variables was carried out in a determined time, the explanatory methodology was based on the variables under study and the field methodology because it was carried out in the place where the problem was found. It was framed in the analytical, inductive-deductive and statistical methods, which contributed to the theoretical foundation, in the correlation between interpersonal relationships and their impact on children's learning, the technique used for the research was the survey and interview as an instrument was used the questionnaire, among the main results could be determined that within the classroom there is no good interpersonal relationship, which hinders student cooperation and the achievement of good grades. Among the conclusions obtained it can be asserted that teachers do not promote an adequate school climate which makes it difficult for students to maintain a good social interaction and cannot achieve the required knowledge, what is recommended is that within the classroom communication standards are promoted so that they can interact and create an atmosphere of work and mutual cooperation. Key words: Interpersonal relationships, school climate, teaching and learning process.